Beyond Gender: Urban-Rural Disparities in Financial Access among Nepali Households - Chhetri, Santosh; Adhikari, Gyan Mani; Adhikari, Prem Lal; Adhikari, Gyanendra (The International Research Journal of Management Science, 2025)
Purpose – This study challenges conventional assumptions about gender barriers in financial inclusion by examining the relative importance of demographic, socioeconomic, and geographic determinants of financial access in Nepal. Design/methodology/approach – We analyze data from 2,643 individuals across 166 communities using the nationally representative Nepal Living Standards Survey-IV (2022-23). Survey-weighted logistic regression models estimate the probability of loan access while controlling for individual, household, and geographic characteristics. Findings – Contrary to widespread assumptions, gender shows no significant effect on financial access (coefficient = 0.082, p = 0.430). Instead, rural residents demonstrate 8.1 percentage points higher probability of accessing loans compared to urban residents (p = 0.004), representing the strongest predictor in our model. Traditional socioeconomic indicators including education, employment status, and income quintiles show minimal explanatory power. Practical implications – Financial inclusion policies should prioritize addressing urban-rural disparities rather than exclusively targeting gender gaps. The rural advantage suggests that microfinance expansion and community-based lending mechanisms may have been more effective than formal banking sector development in expanding access. Originality/value – This research provides the first comprehensive analysis of financial access determinants using Nepal’s latest nationally representative survey data, revealing unexpected patterns that challenge dominant policy narratives about financial inclusion barriers in developing countries.